Clinical characteristics and outcomes of children with cochlear implants who had preoperative residual hearing. (1st February 2022) - Na, Eunjung; Toupin-April, Karine; Olds, Janet; Whittingham, JoAnne; Fitzpatrick, Elizabeth M.
Abstract: Objective: Cochlear implants (CI) candidacy criteria have expanded to include children with more residual hearing. This study explored the clinical profiles and outcomes of children with CIs who had preoperative residual hearing in at least one ear. Design: A retrospective chart review was conducted to collect clinical characteristics and speech perception data. Pre- and post-CI auditory and speech perception data were analysed using a modified version of the Pediatric Ranked Order Speech Perception (PROSPER) score. Study sample: This study included all children with residual hearing who received CIs in one Canadian paediatric centre from 1992 to 2018. Results: A total of 100 of 389 (25.7%) children with CIs had residual hearing (median 77.6 dB HL, better ear). The proportion of children with residual hearing increased from 1992 to 2018. Children who had auditory behaviour and speech perception tests (n = 83) showed higher modified PROSPER scores post-CI compared to pre-CI. Phonologically Balanced Kindergarten (PBK) test scores were available for 71 children post-CI; 81.7% (58/71) of children achieved > 80% on the PBK. Conclusions: One in four children who received CIs had residual hearing, and most of them had severe hearing loss at pre-CI. These children showed a high level of speech perception with CIs.